Strategi Pick Up Service BMT NU Dalam Meningkatkan Inklusi Keuangan Dan Motivasi Menabung Masyarakat Kecamatan Wringin Bondowoso - Iga Ilya Dewi; Nindita Muhafillah; Fina Karmila Mafir; Nur hidayat (CV. ITTC INDONESIA, 2024)
Baitul Maal Wat Tamwil is a microfinance institution that emerged from the active role of the community to improve the economy and improve the welfare of the surrounding community. BMT, which is an extension of banking institutions, supports the distribution of funding to unbankable communities. BMT NU offers several sharia financial products. One of the products that is much in demand by the local community is savings products using the PICK UP SERVICE strategy so this product is interesting to study at BMT NU Wringin Branch, Bondowoso. This Pick up Service strategy makes it easier for customers to save without having to come to the BMT NU office. In this research, normative research methods are used, while the approach used is an analytical approach where the PICK UP SERVICE Strategy is the research object. The results obtained from the pick up service strategy in increasing financial inclusion and customer savings motivation occurred at BMT NU Wringin Branch, Bondowoso. is an effective strategy for marketing because it makes it easier for customers to carry out transactions.